Los desafíos de escenificar el “alma nacional”. Chile en la Exposición Iberoamericana de Sevilla (1929). - Sylvia Dümmer Scheel. (Historia Crítica, 2010)
This article examines Chilean national imaginaries during the 1920s and their graphic and material representation. It does so through a concrete case: the preparations and staging of Chile's pavilion in the Ibero-American Exposition of 1929 in Seville. The study begins by explaining the influence of culturalist nationalism on Chilean imaginaries and the need to represent the "national soul" in the exposition. It then analyzes how these ideas were physically and graphically represented in the country's exhibit. Special attention is paid to the representational challenges and the negotiations between different participants concerning the content of the exhibit.